EVALUATION OF THE PERCENTAGE OF BODY FAT OF THE CITY OF SCHOOL ARAPIRACA/ALAGOAS (Fiep Bulletin - online, 2012)
The aim of this study was to evaluate the fat percentage of students aged 9 to 14 years oldthe city of Arapiraca / Alagoas. Transversal study with descriptive and quantitative approach with a sample of 3,918 students enrolled in 10 schools in the urban area of Arapiraca. Wecollected the values ??for the subscapular skinfold and triceps, and thencalculated the percentage of fat (% BF) using the protocol proposed by Lohman (1992).The results showed high levels of fat percentage of students in both sexes, except for theage of 9 years in females, classified as optimal. It is worth emphasizing the need forcontrol over the daily habits of the students in order to reduce the levels of relative body fat,thereby contributing to reducing the risk of onset of chronic-degenerative and cardiovascular prematurely due to the high rates presented in the study.
Keywords: Fat; School; Assessment.